Is Teaching Less Challenging for Career Switchers? First and Second Career Teachers’ Appraisal of Professional Challenges and Their Intention to Leave Teaching - Troesch, Larissa Maria; Bauer, Catherine Eve (Frontiers in Psychology, 2020)
Teacher attrition is a major problem in many countries. One possible and widely spread counter measure is to recruit persons from other occupational fields to become teachers. Although the existent literature suggests that second career teachers (SCT) have additional resources compared to first career teachers (FTC), empirical data are still scarce on whether SCT are able to transfer prior skills and knowledge into teaching, how this affects the way they deal with professional demands, as well as their intentions to stay in their new profession. On this basis, the present study explores whether first career teachers (FCT) and SCT differ in how challenged they feel by typical professional demands associated with teaching, and in what way their challenge appraisals are relevant for the intention to leave the profession. A questionnaire survey was conducted with a sample of 297 teachers, comprising 193 FCT and 104 SCT. Both groups had had regular teacher training, resulting in a full teacher diploma. Professional demands associated with student learning and assessment were rated as most challenging, whereas classroom management, establishing a professional role and cooperation with colleagues were perceived as less challenging. A group difference was found in professional demands concerning student learning and assessment, where SCT felt less challenged than FCT. Also, SCT were more intent to stay in the teaching profession. Further analyses showed that both group differences are mainly attributable to the higher proportion of male teachers among SCT, as well as to their higher general self-efficacy beliefs. Both career background and the degree to which the teachers felt challenged in their job played a subordinate role for the intention to leave the teaching profession. The findings indicate that SCTs’ background as career switchers might be less important for coping with specific professional demands than the existent research literature implies. On the other hand, they indicate that SCT feel nearly as challenged when starting to teach as traditional teachers, and need may have the same needs for good teacher induction.